2018
DOI: 10.1042/bsr20180915
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA in drug resistance of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has been one of the most highly lethal cancers. The acquisition of drug resistance accounts for the majority of poor effects of chemotherapy in HCC. Non-coding RNAs (ncRNAs) including miRNAs, long ncRNAs (lncRNAs), and circular RNA (circRNA) have been well-documented to participate in cancer occurrence and progression. Recently, multiple studies have highlighted the key roles of ncRNAs in chemoresistance of HCC. In addition, accumulating evidence has demonstrated that they can se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 86 publications
1
70
0
Order By: Relevance
“…As flexible scaffolds, lncRNAs can also absorb different macromolecules, form complexes, and play different biological functions. Many recent reports have revealed that lncRNAs are involved in the multiple biological functions of tumor cells, such as proliferation, invasion, metastasis, and drug resistance [11][12][13][14][15].…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
“…As flexible scaffolds, lncRNAs can also absorb different macromolecules, form complexes, and play different biological functions. Many recent reports have revealed that lncRNAs are involved in the multiple biological functions of tumor cells, such as proliferation, invasion, metastasis, and drug resistance [11][12][13][14][15].…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
“…11 CircRNAs may also play a key role in the development of drug resistance. Recently, multiple studies have highlighted the key roles of ncRNAs in chemoresistance of cancer, such as HCC, 142,249 lung cancer, 250,251 gastric cancer, 252,253 breast cancer, 254,255 multiple myeloma, 256 acute myeloid leukemia, 234 prostate cancer, 257 bladder cancer, 258 among others. The up-to-date information regarding the role of circRNAs in the resistance of tumors to chemotherapy has been recently summarized with multiple mechanisms, such as modulating various regulatory pathways and processes including the ceRNA regulatory network axis, EMT process, regulation of ABC transporters, apoptosis, autophagy, and CSCs, among others although many physiological processes and biological signaling pathways through which circRNAs are involved in drug resistance still remained unknown.…”
Section: Discussion and Prospectivementioning
confidence: 99%
“…137 Overall, circRNAs played key roles in tumorigenesis and development, epigenetic regulation, drug resistance, and could be considered as immune-associated biomarker and therapeutic target in HCC. [138][139][140][141][142][143][144] Regardless, more in-depth study of circRNA biofunctions in HCC is greatly desired.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…A number of research teams have demonstrated the involvement of lncRNAs in chemoresistance and chemosensitivity of different types of cancer [222][223][224][225][226][227]. In osteosarcoma, chemotherapy plays an important role, but its efficacy is limited by acquired resistance to different chemotherapeutic drugs, mainly cisplatin and doxorubicin [228].…”
Section: Lncrnas As Predictive Biomarkers and Drug Resistance In Ostementioning
confidence: 99%